VALUE-BASED LEADERSHIP DEVELOPMENT: A CASE STUDY FROM PT XYZ - Saputra, Nopriadi (Review of Management and Entrepreneurship, 2018)
The main challenge of family business is about sustainability. Sustaining the success of business across the next generations is a critical issue. By using a case study from an Indonesia family business, this study aims (1) to measure the level of leadership capability of the existing management team, (2) to identify the relevant values to develop so that redefined visions and missions, (3) to define developmental program of the value based leadership for the existing management team. This study used mixed research method using an appreciative inquiry for the qualitative and descriptive statistics for the quantitative approach. The conclusions of this study are: (1) the company need to increase the leadership capacity for the existing management team, (2) there are seven relevant values for enabling the new vision and mission: ownership, responsibility, integrity, creativity, learning, quality and consistence, (3) The management team are expected to play leadership role as a protector, promoter and role model for actuating those seven values, especially on values such as consistence, creativity, learning and quality.